2008
DOI: 10.4103/0255-0857.40526
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of bacterial vaginosis among young women of reproductive age in Mysore, India

Abstract: Purpose-Bacterial vaginosis (BV) is the most common cause of abnormal vaginal discharge among women of childbearing age and is associated with STI/HIV and adverse birth outcomes. The objective of this study was to determine the prevalence and correlates of BV among young women of reproductive age in Mysore, India. Methods-Between October 2005 and December 2006, 898 sexually active women of 15-30 years of age were enrolled from two reproductive health clinics in Mysore. The women underwent an interview followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
43
1
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 20 publications
6
43
1
5
Order By: Relevance
“…Maximum cases of symptomatic vaginal discharge were observed between 21 and 30 year of age (46%). Similar peak age incidence (15-30 years 82.8%) is noted in other studies done by Rekha et al, Singh et al, and Madhivanan et al, [1,8,9]. Out of 100 cases homogenous discharge was most prevalent (52%), followed by mucopurulant discharge in 23% of women.…”
Section: Discussionsupporting
confidence: 85%
“…Maximum cases of symptomatic vaginal discharge were observed between 21 and 30 year of age (46%). Similar peak age incidence (15-30 years 82.8%) is noted in other studies done by Rekha et al, Singh et al, and Madhivanan et al, [1,8,9]. Out of 100 cases homogenous discharge was most prevalent (52%), followed by mucopurulant discharge in 23% of women.…”
Section: Discussionsupporting
confidence: 85%
“…This is comparable to previously obtained measures of HSV-2 prevalence among other pregnant women in India [16,17]. The 6.7% prevalence is lower than the three previously obtained estimates of HSV-2 prevalence in the state of Karnataka, which ranged from 10.9 to 18.9% [20][21][22] although these studies focused on nonpregnant populations. Almost all the women in this study reported having a single sex partner in their lifetime and one woman reported being unmarried.…”
Section: Discussionsupporting
confidence: 83%
“…The prevalence of BV varied considerably (5 to 30%) among different studies (Bradshaw et al, 2005). Our observed prevalence was similar to those reported by Madhivanan et al, (2008), Akhter et al, (2010) and Mengistie et al, (2013) in India (19.1%), Bangladish (21%), and Ethiopia (19.4%), respectively. However, lower prevalence of BV was reported in France (7.1%) (Desseauve et al, 2012), Turkey (7.76%) (Haltas et al, 2012) and Pakistan (10.8%) (Taj et al, 2014).…”
Section: Prevalence Of Bv Among the Studied Patientssupporting
confidence: 90%